2019
DOI: 10.12965/jer.1836542.271
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the back school program on the low back pain and functional disability of Iranian nurse

Abstract: Low back pain (LBP) as a recurrent and costly health problem and one of the leading causes of disability, is common in nurses. It can have adverse effects on the quality of life of nurses and quality of care of patients. The aim of the study was to evaluate the effectiveness of Back School program on the LBP and functional disability of Iranian nurses. A quasi-experimental methodological design was utilized for this study. Participants were nurses with back pain who participated in the Back School program work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 25 publications
(36 reference statements)
2
39
0
3
Order By: Relevance
“…China [12,[16][17][18][19][20][21][22][23][24][25][26][27]], 6 from Iran [13,14,[28][29][30][31], 2 from the USA [32,33], and 2 from Hungary [34,35]. One study originated from each of the following countries:…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…China [12,[16][17][18][19][20][21][22][23][24][25][26][27]], 6 from Iran [13,14,[28][29][30][31], 2 from the USA [32,33], and 2 from Hungary [34,35]. One study originated from each of the following countries:…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Many studies have shown that NSCLBP can be relieved by many types of non-drug interventions, such as yoga, low back exercise, physical exercise, multidisciplinary intervention, cognitive behavioral therapy, and health education [12][13][14]. However, the optimal choice is still unclear, which raises some challenges for nurses to manage NSCLBP with non-drug interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As LBP is the most common work‐related health problem, unsurprisingly there is a high prevalence among healthcare employees, especially nurses (Hignett, 1996; June & Cho, 2011; Yassi & Lockhart, 2013). The overall prevalence of LBP among nurses ranges from 35%–80% (Járomi et al., 2018; Pakbaz et al., 2019; Parreira et al., 2017; Soroush et al., 2018; Van Hoof et al., 2018). The prevalence of LBP in Iranian nurses was reported to be 64.8% (Mohammadi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…-Seleção de artigos com estratégias reabilitativas complementares, a intervenção utilizada, número de participantes, principais resultados e Nível de Evidência (NE), Florianópolis, SC, Brasil, 2019Quadro 4 -Seleção de artigos com estratégias combinadas, a intervenção utilizada, número de participantes, principais resultados e Nível de Evidência (NE), Florianópolis, SC, Brasil, 2019 , 2020 internacionais, mas todas de delineamento experimental6,[15][16][17][18][19][20][21][22] e quase experimental3,[13][14]23 de ensaios clínicos, com exceção de uma revisão sistemática;4 desenvolvidas, principalmente, nos locais de trabalho, geralmente hospitais,3,[13][14][15]18,[20][21][22][23] uma clínica16 e três instituições universitárias 6,19,22. DiscussãoConstatado que, entre os recursos existentes, principalmente fisioterapêuticos, poucos têm sido utilizados em profissionais de enfermagem.…”
unclassified
“…Da mesma forma, o programa diminuiu os escores de dor lombar no grupo intervenção e os níveis Prevenção e reabilitação da dor lombar em trabalhadores de enfermagem: revisão...| 14 , 2020 de incapacidade funcional medidos pelo Roland Morris Disability Questionnaire e também recomendam utilizá-lo no ambiente hospitalar 23. Pesquisas adicionais e futuras devem ser realizadas para comprovação dos efeitos do programa 32.…”
unclassified